2017
DOI: 10.1055/s-0036-1597684
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Visual Assessment Tool to Facial Linear Scars

Abstract: Previous scar scales have focused on verbal descriptions. A nonverbal visual assessment tool would provide a simple way for patients and physicians to quantify scar appearance. The authors sought to use a validated visual assessment tool for linear surgical scars to assess linear scars on the face and to determine whether patients and surgeons rate scars similarly. A total of 143 patients with linear facial scars resulting from repair of Mohs micrographic surgery defects used the visual assessment tool to rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…When assessing scars, their size, color, contour, height (thickness), surface area, surface texture, pliability, location, and subjective symptoms such as itching and pain, and also patient’s perception should be taken into account. It has been indicated that this subjective component of the patient’s view of the scar is as important as objective aspect and it may be very influential in determining the patient’s quality of life (73, 74). Assessment of the scars is a frequent topic of discussion among clinicians because there is no generally accepted evaluation tool, although various ones have been proposed (7577).…”
Section: Scar Evaluationmentioning
confidence: 99%
“…When assessing scars, their size, color, contour, height (thickness), surface area, surface texture, pliability, location, and subjective symptoms such as itching and pain, and also patient’s perception should be taken into account. It has been indicated that this subjective component of the patient’s view of the scar is as important as objective aspect and it may be very influential in determining the patient’s quality of life (73, 74). Assessment of the scars is a frequent topic of discussion among clinicians because there is no generally accepted evaluation tool, although various ones have been proposed (7577).…”
Section: Scar Evaluationmentioning
confidence: 99%